Peningkatan Hasil Belajar Tema 7 Melalui Discovery Learning Berbantu Permainan Orang-Orangan pada Peserta Didik Kelas IV SDN Gajahmungkur 04 Semarang - Leviatun Khasanah; Ganis Suprihartini (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
Conventional learning causes the learning outcomes of the theme of 7 students to be still low, especially in the content of Indonesian and social studies. This class action research was carried out aimed at improving learning outcomes through the Discovery Learning model aided by the puppeteer's pupils playing class IV SDN Gajahmungkur 04 Semarang. Discovery learning is a learning model that emphasizes students discovering their own knowledge through active learning. Scarecrow is a game that pairs images that are adapted to the diversity of Indonesian culture. The research subjects were class IV totaling 34 children. The study was conducted in two cycles with two meetings per cycle. Data collection uses observation, written tests, and documentation. Data analysis uses quantitative and qualitative analysis. The results showed an increase in Indonesian mupel learning outcomes from cycle I with a graduation percentage of 50% to 94% in cycle II, whereas in IPS mupel from cycle I with a percentage of graduation 44% to 91% in cycle II. Student activity has increased from cycle I with a score of 610 to 762 in cycle II. Teachers' teaching skills have improved from cycle I with a score of 93 (Fair) to 128 (Very Good). Based on the results of classroom action research that has been carried out it can be concluded that the Discovery Learning model assisted by a puppet game can improve the results of student learning activities as well as teacher teaching skills.